2023
DOI: 10.3390/pr11010272
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Biological Studies of Synthesized Titanium Dioxide Nanoparticles from Leaf Extract of Juniperus phoenicea (L.) Growing in Taif Region, Saudi Arabia

Abstract: Green synthesis of metal nanoparticles in nanosized form has acquired great interest in the area of nanomedicine as an environmentally friendly and cost-effective alternative compared to other chemical and physical methods. This study deals with the eco-friendly green synthesis of titanium dioxide nanoparticles (TiO2 NPs) utilizing Juniperus phoenicea leaf extract and their characterization. The biosynthesis of TiO2 NPs was completed in 3 h and confirmed by UV-Vis spectroscopy, a strong band at 205.4 nm distin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…After getting attached, two or more than two particles give this effect [22]. The Selected Area Electron Diffraction (SAED) pattern of both the TiO 2 chemically synthesized and green synthesized confirmed that the nanoparticles vibration [19,45]. In green synthesized TiO 2 NPs, the peek obtained at 2926 cm −1 also showed O-H stretching, but the visible intensity of the peak is medium.…”
Section: Transmission Electron Microscopy Analysis Of Tio 2 Nanoparticlementioning
confidence: 92%
See 4 more Smart Citations
“…After getting attached, two or more than two particles give this effect [22]. The Selected Area Electron Diffraction (SAED) pattern of both the TiO 2 chemically synthesized and green synthesized confirmed that the nanoparticles vibration [19,45]. In green synthesized TiO 2 NPs, the peek obtained at 2926 cm −1 also showed O-H stretching, but the visible intensity of the peak is medium.…”
Section: Transmission Electron Microscopy Analysis Of Tio 2 Nanoparticlementioning
confidence: 92%
“…Surface properties such as morphology, shape and size of nanoparticles were determined with the help of scanning electron microscopy (SEM) [19]. Figure 2 is the SEM image of the chemically synthesized and green synthesized TiO 2 nanoparticles.…”
Section: Scanning Electron Microscopy (Sem) Of Tio 2 Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations